Role of Mitochondrial Ca(2+) Homeostasis in Cardiac Muscles - Cao, Jessica L. (Arch Biochem Biophys, 2019)
Recent discoveries of the molecular identity of mitochondrial Ca(2+) influx/efflux mechanisms have placed mitochondrial Ca(2+) transport at center stage in views of cellular regulation in various cell-types/tissues. Indeed, mitochondria in cardiac muscles also possess the molecular components for efficient uptake and extraction of Ca(2+). Over the last several years, multiple groups have taken advantage of newly available molecular information about these proteins and applied genetic tools to delineate the precise mechanisms for mitochondrial Ca(2+) handling in cardiomyocytes and its contribution to excitation-contraction/metabolism coupling in the heart. Though mitochondrial Ca(2+) has been proposed as one of the most crucial secondary messengers in controlling a cardiomyocyte’s life and death, the detailed mechanisms of how mitochondrial Ca(2+) regulates physiological mitochondrial and cellular functions in cardiac muscles, and how disorders of this mechanism lead to cardiac diseases remain unclear. In this review, we summarize the current controversies and discrepancies regarding cardiac mitochondrial Ca(2+) signaling that remain in the field to provide a platform for future discussions and experiments to help close this gap.